2012
DOI: 10.1021/ja210126j
|View full text |Cite
|
Sign up to set email alerts
|

Heme Reactivity is Uncoupled from Quaternary Structure in Gel-Encapsulated Hemoglobin: A Resonance Raman Spectroscopic Study

Abstract: Encapsulation of hemoglobin (Hb) in silica gel preserves structure and function, but greatly slows protein motion, thereby providing access to intermediates along the allosteric pathway that are inaccessible in solution. Resonance Raman (RR) spectroscopy with visible and ultraviolet laser excitation provides probes of heme reactivity and of key tertiary and quaternary contacts. These probes were monitored in gels after deoxygenation of oxyHb and after CO binding to deoxyHb, which intiate conformational change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 74 publications
(182 reference statements)
2
51
0
Order By: Relevance
“…Our calculations of oxygen affinity and populations of tertiary conformations show that only the TTS model is consistent with the experimental results. oxygen binding to hemoglobin single crystals (26,27), first carried out by Mozzarelli et al (28), and to hemoglobin encapsulated in silica gels, a method introduced by Shibayama and Saigo (29), where one quaternary structure is stable for hours to days (30,31). The single-crystal binding experiments showed that oxygen binding to the T quaternary structure is noncooperative (Fig.…”
Section: Introductionmentioning
confidence: 98%
“…Our calculations of oxygen affinity and populations of tertiary conformations show that only the TTS model is consistent with the experimental results. oxygen binding to hemoglobin single crystals (26,27), first carried out by Mozzarelli et al (28), and to hemoglobin encapsulated in silica gels, a method introduced by Shibayama and Saigo (29), where one quaternary structure is stable for hours to days (30,31). The single-crystal binding experiments showed that oxygen binding to the T quaternary structure is noncooperative (Fig.…”
Section: Introductionmentioning
confidence: 98%
“…The four heme groups are located relatively near the surface of the protein shell the same as the family of peroxidases (Jones et al, 2012;Chen et al, 2009;Scheller et al, 2005;Perutz et al, 1968). In the Hb electrochemistry, it has been believed that the strong adsorption of proteins onto the electrode surfaces brought about a denaturation of the protein structure and slow electron transfer characteristics with the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Spiro and coworkers found that T quaternary structure markers do not appear in the resonance Raman spectra for about 5 days at 22 °C, which is orders of magnitude longer than the longest time of 1,000 s used in the continuous photolysis experiments [128,136]. Additionally, since the Raman experiments were carried out at complete deoxygenation, the observed R T rate is higher than the one observed at partial photolysis, as occurs in the continuous photolysis experiments.…”
Section: Trapping Reaction Intermediates: Inhibition Of Conformationamentioning
confidence: 94%
“…In the case of T state encapsulated Hb allosteric effects have also been evidenced [57,58]. Monitoring the changes in the optical or resonance Raman spectra of R-state oxy-Hb gels after complete removal of oxygen demonstrated that the R T transition for the fully unliganded Hb can be slowed down by up to 10 orders of magnitude [58,80,83,92,[126][127][128]. Thus, the R T transition is not prevented by the gel matrix, rather slowed down by several orders of magnitude so that intermediate short lived Hb states, that are unstable in aqueous solutions, can be investigated with conventional spectroscopic techniques.…”
Section: Trapping Reaction Intermediates: Inhibition Of Conformationamentioning
confidence: 97%